Gaze Cueing by Pareidolia Faces. (December 2013) - Takahashi, Kohske; Watanabe, Katsumi
Visual images that are not faces are sometimes perceived as faces (the pareidolia phenomenon). While the pareidolia phenomenon provides people with a strong impression that a face is present, it is unclear how deeply pareidolia faces are processed as faces. In the present study, we examined whether a shift in spatial attention would be produced by gaze cueing of face-like objects. A robust cueing effect was observed when the face-like objects were perceived as faces. The magnitude of the cueing effect was comparable between the face-like objects and a cartoon face. However, the cueing effect was eliminated when the observer did not perceive the objects as faces. These results demonstrated that pareidolia faces do more than give the impression of the presence of faces; indeed, they trigger an additional face-specific attentional process.